The Relationship Among Perceived Transformational Leadership, Work Motivation, and Individual Performance: A Study at PT Jakarta Railway - Annisa Arnindita; Achmad Fajar Hendarman (Green Publisher Indonesia, 2026)
This study investigates the relationship among transformational leadership, work motivation, and individual performance at PT Jakarta Railway, a government-owned urban transport operator undergoing organisational change. As demands for reliable and sustainable public transport services increase, leadership and employee motivation become essential drivers of performance. However, studies examining these relationships in Indonesian public transport organisations remain limited. This research aims to address the gap by analysing how employees' perceptions of transformational leadership and their work motivation influence performance across three directorates. Using a quantitative design, data were collected through structured questionnaires, generating 235 valid responses. Transformational leadership was measured using the Multifactor Leadership Questionnaire (MLQ), work motivation with the Work Extrinsic and Intrinsic Motivation Scale (WEIMS), and performance using a 23-item instrument. Statistical assumptions were met, and simple and multiple linear regression analyses were conducted using SPSS. The findings show that transformational leadership has a strong and significant positive effect on individual performance. Employees who perceive their leaders as inspiring, supportive, and clear in direction tend to show better performance. Work motivation also positively affects performance, although its influence becomes weaker when leadership is included in the model, indicating that leadership is the stronger predictor. When tested together, transformational leadership and motivation significantly predict performance, explaining 12% of the variance. Demographic factors did not substantially affect the model. Overall, the study highlights the central role of transformational leadership in enhancing employee performance at PT Jakarta Railway and provides practical implications for leadership development and performance management within public transport organisations.